Planetary health and the role of community health workers - Manas R Behera; Deepanjali Behera; Sudhir K Satpathy (Journal of Family Medicine and Primary Care, 2020)
In this era, grand challenges lies in biodiversity loss, climate change, and global noncommunicable diseases signify that planet and humanity are in crisis. Scholarly evidence from human and animal kingdom suggest that there is an optimism in planetary health which can provide a unique and novel concept where efforts toward survival and remediation can be made. With accurate navigation, the current challenges can be mitigated leading to a new reality, one in which the core value is the well-being of all. This paper discusses the drivers of planetary health and the role of community health workers (CHWs) in making health-care system more resilient that can produce multiple benefits to community and overall planetary health. A web-based international database such as Google, Google Scholar, SCOPUS/MEDLINE/PubMed, and JSTOR was searched relevant to a planetary health framework. The study findings suggest that CHWs can offer health care interventions through environmental health cobenefits across the spectrum of health effects of climate change cause and effects. These actions have been divided into four major categories (i. health care promotion and prevention, ii. health care strengthening, iii. advocacy, and iv. education and research) that CHWs perform through a variety of roles and functions they are engaged in protecting planetary health. CHWs contribute toward achieving sustainable development goals such as planetary health and focus on environment sustainability and well-being of entire mankind.